Localizzazione dei diritti o localismo dell’appartenenza? Abbozzo di una teoria della residenza - Gargiulo, Enrico (SocietàMutamentoPolitica, 2011)
The aim of this article is to investigate the nature and the specificities of a new status that, as a consequence of the current ‘crisis’ of national citizenship, is purchasing an increasing importance: residence. More in detail, the object of this paper is constituted by the attempt to understand whether the process of ‘location of the rights’ that is taking place in many European states, and particularly in the Italian context, is shaping an inclusionary system of ‘local citizenships’ or, rather, an exclusionary one, based on a particularistic idea of membership.